Correction: Implementation and Evaluation of Obstetric Early Warning Systems in Tertiary care Hospitals. - PLOS Global Public Health Staff (Public Library of Science (PLoS), 2023)
[This corrects the article DOI: 10.1371/journal.pgph.0000225.].